1994
DOI: 10.1007/bf02239908
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei, T. congolense andT. vivax infections in horses on a farm in Kenya

Abstract: Equines are particularly susceptible to infection with Trypanosoma evansi and T. brucei, but rarely is natural T. congolense and T. vivax infection seen in horses. An outbreak of trypanosomosis occurred in a herd of horses used for patrolling the pineapple fields on the Del Monte Farm, Thika, Kenya initially involving 6 horses. On subsequent screening of the entire group, T. brucei, T. congolense and T. vivax infections were detected in 16 of the 35 horses. The tests used for diagnosis included microscopic exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Trypanosoma b. brucei is found in various domestic ungulates but it is particularly virulent in dogs, camels and horses, the latter often succumbing to infection within a few months in the absence of treatment. In areas where more than one trypanosome species is present, mixed infections in domestic animals are often encountered (Kihurani et al 1994; Auty et al 2008; Biryomumaisho et al 2013; Takeet et al 2013; Moti et al 2015) and modern molecular techniques (Desquesnes and Davila, 2002) facilitate speciation. Many wild animal species in Africa also host one or more trypanosome species and can serve as reservoirs for both human and domestic animal infective trypanosomes (Mulla and Rickman, 1988; Auty et al 2012).…”
Section: The Animal Trypanosomiases: Distribution Transmission Hostmentioning
confidence: 99%
“…Trypanosoma b. brucei is found in various domestic ungulates but it is particularly virulent in dogs, camels and horses, the latter often succumbing to infection within a few months in the absence of treatment. In areas where more than one trypanosome species is present, mixed infections in domestic animals are often encountered (Kihurani et al 1994; Auty et al 2008; Biryomumaisho et al 2013; Takeet et al 2013; Moti et al 2015) and modern molecular techniques (Desquesnes and Davila, 2002) facilitate speciation. Many wild animal species in Africa also host one or more trypanosome species and can serve as reservoirs for both human and domestic animal infective trypanosomes (Mulla and Rickman, 1988; Auty et al 2012).…”
Section: The Animal Trypanosomiases: Distribution Transmission Hostmentioning
confidence: 99%
“…also reported outbreaks in sheep and goats in the Brazilian semi-arid region. To the authors knowledge, the infection by T. vivax in equines was not reported in Brazil until the present study, but in Africa, it is often reported causing disease in horses and donkeys in single or mixed infections with Trypanosoma congolense, Trypanosoma evansi, and Trypanosoma brucei (Kihurani et al 1994;Faye et al 2001;Dhollander et al 2006;Auty et al 2008;Pinchbeck et al 2008).…”
Section: Introductionmentioning
confidence: 59%
“…Natural infections by T. vivax in horses, donkeys, and mules are common in West Africa (Kihurani et al 1994;Faye et al 2001;Dhollander et al 2006;Pinchbeck et al 2008) and are also reported in East Africa (Auty et al 2008;Abebe and Wolde 2010). To our knowledge, the infection by T. vivax had not been reported in South American equines before this study.…”
Section: Discussionmentioning
confidence: 99%
“…All data analyzed in this paper are provided as supplementary le. [6,43,86,87,92,98,101,103,107,[113][114][115]44,122,142,144,145,152,[178][179][180][181][182]48,184,187,191,229,230,240,248,257,258,262,64,[264][265][266]69,70,[74][75][76] French Guiana [66,146,209,227,261,267,275,172,174,…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%